EFEKTIVITAS PROGRAM MICRO TEACHING BAGI GURU BAHASA ARAB DI PESANTREN AR-RAUDHATUL HASANAH MEDAN - Imam Tazali (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2020)
The purpose of this study was to determine the application of learning Arabic language sapport using micro teaching program on learning the Arabic language the application of micro teaching program in Arabic language learning aimed to the ability of Arabic teacher in Islamic Boarding School in the Arabic language support. The research concludes that the implementation of micro teaching program for Arabic language teacher in Islamic boarding is planning based on the concept plan include formulating learning goals. This program to increase the competency Arabic language for Islamic pupil in the learnig process and impraving the ability of student to understand the material contained within each core discussion of Arabic language teacher preparation, class preparation, measure of student learning activities and evaluation learning. The application of this methods is conversation learning tools, speech, discussion and writing. In this activity using interviews and testing program with the audio target that is expected the and of the activities is assessed with decription maturity of learning Arabic language. The teacher capacity or ability of Arabic language is to caltivate the spirit of love for the Arabic teacher improving quality and provide the positive effects and give the comprehensive and developed the teaching concept.